Digital design principles and computer architecture - Karalis, Edward (Prentice Hall, 1997)
Based on the author's 20+ years of hands-on experience, this book articulates the underlying principles and practices that comprise today's digital components and systems. Karalis provides a comprehensive yet concise, fully integrated treatment of relevant analytical tools and design methodologies as applied to various integrated devices, modules and signal interactions. Coverage offers a balance of theory, application and functional level examples.